A National Survey into referral and training in the management of oesophageal perforation in the United Kingdom (The International Journal for Scientific Research, 2025)
Background: Over the last 30 years, oesophageal surgery amongst thoracic surgeons has reduced by 80%, and forms less than 1% of current thoracic practice. Oesophageal perforation has a high morbidity, and mortality rates can be as high as 30% if not treated. There are currently no guidelines regarding referral for the management of oesophageal perforation in the UK. Methods: We designed an online survey to ascertain the current expert opinion on the management of oesophageal perforation, which was validated and approved by the society of cardiothoracic surgery of Great Britan and Ireland- SCTS. This was sent to all consultant thoracic (N=77) and cardiothoracic (N=85) surgeons identified in the SCTS registry. In total, 49 responses were received from a variety of UK regions. Results: Many responses indicated that emergency cover for oesophageal perforation came exclusively from the upper gastrointestinal (GI) surgeons (50%) compared to thoracic surgeons (18%). Only 37% agreed they would manage the patients themselves and a similar number were comfortable to operate alone. 46% of believed the service should be taken over exclusively by the UGI surgeons. With regards to surgical experience: 55% agreed they could comfortably deal with complex cases, which correlated with having >16 years experience. Only 25% of consultants with 1-5 years experience felt confident to manage the condition alone. With regards to previous training, 100% of consultants who trained >16 years ago believed they had sufficient exposure to oesophageal surgery as a trainee, compared to 50-70% for those trained
Keywords: Oesophageal Perforation; Referral; Training; United Kingdom